2012
DOI: 10.1097/mop.0b013e3283527035
|View full text |Cite
|
Sign up to set email alerts
|

Blunt cervical spine injury in children

Abstract: Evidence in the management of children with CSI has expanded in recent years, but further large prospective studies are needed. We present a review of some recent developments influencing clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…[177][178][179][180][181] Several low-risk prediction rules have been developed to avoid unnecessary prehospital spinal immobilization in children, but have proven difficult to validate, because these injuries are so uncommon. 186 …”
Section: Specific Pediatric Concernsmentioning
confidence: 99%
See 3 more Smart Citations
“…[177][178][179][180][181] Several low-risk prediction rules have been developed to avoid unnecessary prehospital spinal immobilization in children, but have proven difficult to validate, because these injuries are so uncommon. 186 …”
Section: Specific Pediatric Concernsmentioning
confidence: 99%
“…186 Moreover, most of the foundation for prehospital treatment of children with CSIs is based on adult studies, and the evidence favoring current management strategies is therefore even weaker than in adults. 186,187 Pediatric collars are adapted to the size and anatomy of children, whereas undesirable neck flexion on spine boards should be avoided by individual modifications. 188 No studies have been identified that compare spinal stabilization with or without collars in children.…”
Section: Specific Pediatric Concernsmentioning
confidence: 99%
See 2 more Smart Citations
“…In these combined cases, dorsal wire fixation is indicated (Fig. 2,4,13,55,56 A form of AARF is known as Grisel syndrome, named after a French ENT surgeon, and it was first described in 1830. 26,37,[52][53][54] Atlanto-axial Rotatory Fixation AARF is the most common PCSI.…”
Section: Atlanto-occipital Dissociation (Aod)mentioning
confidence: 99%